Retail prices of selected items : january - june 1984 (Lagos : Federal Office of Statistics, 1984)
The objective of the survey was to determine weights for the construction of a national Composite Consumer Price Index
osc 27/03/2019
Arch
Keywords: Consumer price indexes; Nigeria